Healthy working enviroment will affect the performance of employee at TM Berhad / Ibrahim Helmi Abdullah - Abdullah, Ibrahim Helmi (Faculty of Business and Management, 2007)
Healthy working environment is very important to many organizations. A good working environment may propose a good result from the workers towards their working performance. This project paper is to evaluate working environment facilitate by The Telekom Malaysia. The objective of this research is to identify the factors facilitate by The Telekom Malaysia to their workers in order to create a healthy working environment to increase their workers' motivation and performance to achieve company goals.